Seasonal Variability of Freshwater Plumes in the Eastern Gulf of Guinea as Inferred From Satellite Measurements. Issue 5 (6th May 2021) - Houndegnonto, O. J.; Kolodziejczyk, N.; Maes, C.; Bourlès, B.; Da‐Allada, C. Y.; Reul, N.
Abstract: In the eastern Gulf of Guinea (GG), freshwater originated from rivers discharges into the ocean and high precipitation rate are key contributors to the upper ocean vertical density stratification, and play a key role in modulating local air‐sea interactions as well as biogeochemical cycle. Nevertheless, the dynamics of the GG freshwater plumes remain poorly documented because of the scarcity of historical, in situ observations and the lack of an ad hoc satellite‐based analysis in this region. Recent advances in remote sensing capabilities from the Soil Moisture and Ocean Salinity (SMOS) satellite mission offer unprecedented coverage and spatiotemporal resolution of Sea Surface Salinity (SSS) in the GG. Using SMOS SSS and available in situ measurements, the seasonal variability of freshwater plumes and associated physical mechanisms controlling their seasonal cycle are presented and analyzed. Freshwater plumes in the GG follow two dynamical regimes. They present maximum offshore extension during boreal winter and exhibit minimum signature during summer. In the northeastern GG, SSS variability is mainly explained by high precipitation rate and Niger River runoff during winter, while during late summer, SSS is mainly driven by horizontal advection. In contrast, southeast of GG, freshwater plumes are mainly supplied by Congo River runoff. From September to March, SSS variability is driven by zonal advection, with a major contribution from Ekman wind‐driven currents. During spring‐summer, the observed SSS increase is likely explained by entrainment and vertical mixing. SSS budget and freshwater advection processes are discussed in the context of the shallow stratification induced by freshwater. Plain Language Summary: The Gulf of Guinea (GG) receives a large amount of freshwater from Congo and Niger rivers runoff and high precipitation. Since the freshwater is lighter than the seawater, the surface freshwater input is spread within large plumes that impact the upper layer vertical structure. The vertical stratification induced by the freshwater plume strongly impacts the air‐sea heat flux exchanges but also the vertical exchanges of nutrient and organic matter. The eastern GG freshwater plumes remain poorly documented because of the scarcity of historical data in this region. This study, based on recent advancements in remote sensing of the Sea Surface Salinity from the European Space Agency Soil Moisture and Ocean Salinity satellite mission, provides a robust characterization of seasonal variability of freshwater plumes in the eastern GG by describing and quantifying their development, extent and dispersal patterns. The freshwater plumes are mainly supplied by rain (respectively river) input in the northern (respectively southern) part of this region. Their offshore seasonal evolution is mostly driven by surface currents and upward salty water fluxes. Surface wind‐driven currents are also found to play a major role in the freshwater plumes offshore extension. Key Points: The Gulf of Guinea's freshwater plumes spreading is characterized by two regimes: Northwestward (September–January) and Southwestward (January–April) In the eastern Gulf of Guinea, precipitation, river runoff, and horizontal advection are major drivers of the low SSS distribution In the southeastern Gulf of Guinea, the horizontal SSS advection is dominated by Ekman wind‐driven currents